Serum Ferritin in the Pediatric Sleep Clinic: What’s Normal Anyway? - Ingram, David G. (J Clin Sleep Med, 2019)
Ingram DG, Al-Shawwa B. Serum ferritin in the pediatric sleep clinic: what’s normal anyway? J Clin Sleep Med. 2019;15(11):1699–1700.